Privacy versus security concerns in a society with government owned quantum computers - Teo, Bryan Soon Han (Nanyang Technological University, 2021)
The concerns regarding the sanctity of individual privacy versus the importance of communal or national security continue to grow in the information-age. In the midst of all the discussion, one must recall the fabled arrival of the quantum age and quantum technology which will possibly sprout elaborate questions that push the boundaries of each value. This paper will explore whether governments will use quantum computers to invade privacy regardless of moral inclinations by referencing the perennial Ring of Gyges thought experiment. Through the use of Netlogo, a model simulating a society and a government attempting to remove and reform uncompliant citizens has been constructed. The model aims to determine if there exists a morally permissible level of invasion of privacy with respect to the collective welfare of the citizens.